Acetohydroxyacid Synthase (AHAS) Inhibitor‐Based Commercial Sulfonylurea Herbicides as Glutathione Reductase Inhibitors: in Vitro and in Silico Studies. Issue 38 (10th October 2022) - Sel, Sedat; Tunç, Turgay; Ortaakarsu, Ahmet Buğra; Mamaş, Serhat; Karacan, Nurcan; Karacan, Mehmet Sayım
Abstract: In this study, in vitro inhibitory effect of AHAS inhibiting‐based commercial sulfonylurea herbicides on human GR and S. cerevisiae GR was determined by electrochemical method. Our findings, the first report in literature, show that the four commercial herbicides were found to be the inhibitors in the range of 4.90–9.75 μM for ScGR, and in the range of 8.54–18.84 μM for hGR. Global reactivity descriptors (energy gaps, electronegativity, hardness and electrophilicity index) of the herbicides were calculated by DFT/B3LYP/6‐31G(d, p) method in gas phase. The electrochemical behavior of the herbicides was studied by cyclic voltammetry. Single‐electron half‐wave reduction potentials and global reactivity descriptors were correlated with the IC50 values of the herbicides. Molecular docking analysis using Schrödinger Suite was applied to examine the interaction between the herbicides and human GR (PDB ID:1XAN and 2GH5), S. cerevisiae GR (PDB ID:2HQM), P. falciparum GR (PDB ID:1ONF), C. albicans AHAS (PDB ID:6DEL) and ScAHAS (PDB ID: 5FEM. Based on the docking results, it can be predicted that (a) herbicides have similar binding potential to two different binding sites of hGRs, (b) herbicides may have antimalarial potential against P. falciparum (c) herbicides may have antifungal potential against C. albicans . Abstract : in vitro  inhibitory effect of AHAS inhibiting‐based commercial sulfonylurea herbicides on human GR and S. cerevisiae GR was determined by volltammetric method. Global reactivity descriptors of the herbicides were calculated by DFT/B3LYP/6‐31G(d, p) method. Molecular docking analysis using Schrödinger Suite was applied to examine the interaction between the herbicides and human GR, S. cerevisiae GR, P. falciparum GR (PDB ID:1ONF), C. albicans AHAS  and ScAHAS.